Predictive scale of mortality due to cardiovascular affection in elderly from Santiago de Cuba municipality - Naifi Hierrezuelo Rojas; German Del Rio Caballero; Alfredo Hernández Magdariaga; Rolando Bonal Ruiz; Consuelo Acosta Lee (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: In the context of healthy aging, the prevention of cardiovascular diseases is a challenge. Objective: To design a scale, based on identified risk factors, for predicting mortality due to cardiovascular affection in elderly. Methods: An analytic, observational and retrospective case-control study was carried out that included 536 elderly over 60 years, belonging to 3 health areas (Ramón López Peña, Municipal and 28 de Septiembre polyclinics) from Santiago de Cuba municipality, during 2021. The scale was derived from the analysis of binary logistical regression of the identified cardiovascular risk factors. Results: As the score of the scale increased, the percentage of dead patients increased. The area under the curve was of 0.836 (p = 0.000) and in the Hosmer-Lemeshow test was obtained p = 1.000. Conclusions: The proposed scale allowed predicting mortality due to cardiovascular affection in elderly, with very good discrimination capacity and calibration.